The Effect of Education on Fertility: Evidence from a Compulsory Schooling Reform - Kamila Cygan-Rehm; Miriam Maeder (Friedrich-Alexander-Universität Erlangen-Nürnberg, Bavarian Graduate Program in Economics (BGPE), 2012)
This study analyzes the effect of education on the number of children, childlessness, and the timing of births. We use exogenous variation from a mandatory reform of compulsory schooling in West Germany to deal with the endogeneity of schooling. In contrast to studies for other developed countries, we find a significant negative effect of education on fertility. This negative effect seems to operate mainly through a postponement of first births away from the teenage years. In addition, education reduces the probability of first motherhood among women in their early 30s. We attribute these findings to the particularly high opportunity costs of child-rearing in Germany.
Keywords: I21; J13; J24; 330; fertility; education; timing of births; childlessness; educational reform; Fruchtbarkeit; Bildungsniveau; Schulbesuch; Schätzung; Alte Bundesländer